PEDAGOGICAL CONDITIONS FOR IMPLEMENTATION OF INTERACTIVE TEACHING METHODS IN PRIMARY GRADES - I.A. Kravtsova; L.O. Horbatenko (Academy of Cognitive and Natural Sciences, 2009)
The article deals with the problem of pedagogical conditions for putting o practice interactive methods of teaching in primary-school classes. The ways of improving the lesson, which are in the close interrelation with the organizational forms of younger schoolchildren learning activities in modern didactics are shown.